2005
DOI: 10.1080/10253890500504557
|View full text |Cite
|
Sign up to set email alerts
|

Role of stress, corticotrophin releasing factor (CRF) and amygdala plasticity in chronic anxiety

Abstract: Stress initiates a series of neuronal responses that prepare an organism to adapt to new environmental challenges. However, chronic stress may lead to maladaptive responses that can result in psychiatric syndromes such as anxiety and depressive disorders. Corticotropin-releasing factor (CRF) has been identified as a key neuropeptide responsible for initiating many of the endocrine, autonomic and behavioral responses to stress. The amygdala expresses high concentrations of CRF receptors and is itself a major ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
159
1
5

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(172 citation statements)
references
References 152 publications
7
159
1
5
Order By: Relevance
“…29 Animal studies demonstrated that activation of N-methyl-D-aspartate glutamate receptors inhibits neurogenesis in the hippocampus 30 and increases the excitability of amygdala neurons. 31 In contrast, it can be argued that pre-existing small hippocampal and amygdalar size increases the risk of developing anxiety or affective disorders. A twin study investigating hippocampal size in Vietnam veterans suggested that individuals with smaller hippocampal size were at greater risk for developing PTSD, 10 rendering it likely that genetic factors contribute to the small hippocampal size of individuals with PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…29 Animal studies demonstrated that activation of N-methyl-D-aspartate glutamate receptors inhibits neurogenesis in the hippocampus 30 and increases the excitability of amygdala neurons. 31 In contrast, it can be argued that pre-existing small hippocampal and amygdalar size increases the risk of developing anxiety or affective disorders. A twin study investigating hippocampal size in Vietnam veterans suggested that individuals with smaller hippocampal size were at greater risk for developing PTSD, 10 rendering it likely that genetic factors contribute to the small hippocampal size of individuals with PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…However, more complex auditory stimulation in the PPI paradigm revealed impaired sensory habituation and/or response inhibition. Anxiety levels were increased in VPA-treated offspring, which indicated abnormal amygdala processing (Shekhar et al, 2005).…”
Section: Behavioral Validation Of the Vpa Model Of Autismmentioning
confidence: 97%
“…Furthermore, for the first time we demonstrate that the activation of Y 1 Rs decreases NMDA-mediated currents, an important new finding with implications for the role of NPY in modulating not only excitability but also synaptic plasticity within the BLA. We have previously shown that CRF-and stress-induced synaptic plasticity within the BLA may be a key component of the pathophysiology of several chronic anxiety disorders, including panic and posttraumatic stress disorder (Rainnie et al, 2004;Shekhar et al, 2005). Stress-induced plasticity within the BLA is mediated by the activation of NMDA receptors and pre-treatment with an NMDA receptor antagonist blocks such plasticity (Rainnie et al, 2004).…”
Section: Implications Of Y 1 R-mediated Increases Of Gaba a -Mediatedmentioning
confidence: 99%
“…The amygdala is a crucial region in the brain circuitry implicated in many of these psychiatric syndromes and is a well-known component of fear, anxiety, and memory circuits (Fendt and Fanselow, 1999;LeDoux, 2000;Maren and Quirk, 2004;Pare et al, 2004;Shekhar et al, 2005). NPY and its receptors are present in the amygdala (Holmes et al, 2003;Kask et al, 2002;Kishi et al, 2005;Wolak et al, 2003), leading to the hypothesis that the anxiolytic-like effects of NPY are mediated in part by the amygdala.…”
Section: Introductionmentioning
confidence: 99%